Examining the Multifaceted Determinants of Antenatal Care Utilization through Structural Equation Modelling: Insights for Maternal Health Interventions - Sam, Napoleon Bellua; Aboyine, Thomas; Tackie-Otoo, Theresah (European Scientific Journal, ESJ, 2024)
Scope and Aims: Maternal and newborn mortality remain critical global public health challenges, especially in underdeveloped countries. One of the most effective strategies for reducing these mortality rates is the proper utilization of antenatal care (ANC). This study investigates the factoras influencing ANC utilization and aims to predict the demographic characteristics that impact ANC attendance using Structural Equation Modeling (SEM). Methods: A descriptive cross-sectional survey was conducted with 254 pregnant women at St. Lucas Hospital in Ghana. Data were collected using a structured questionnaire. Structural Equation Modeling (SEM) and Chi-square analysis were employed to model and examine the factors influencing antenatal care utilization. Results: The findings reveal that the majority (72%) of postpartum mothers had four or more ANC visits during their most recent pregnancy, with 47.6% initiating ANC attendance in the first trimester. Significant demographic factors associated with ANC utilization included maternal education level (P = 0.000), occupational status (P = 0.000), age (P = 0.030), marital status (P = 0.034), religious affiliation (P = 0.000), husband’s education (P = 0.000), and husband’s occupation (P = 0.000). Additionally, SEM analysis indicated that health provider factors (P = 0.000) and community factors (P = 0.005) play a critical role in ANC utilization, while individual factors (P = 0.067) and quality of care factors (P = 0.079) were not statistically significant. Conclusion: This study emphasizes the importance of health provider and community factors in the utilization of ANC services. The findings also highlight that nearly all demographic characteristics, including both the mother’s and husband’s education and occupation, are crucial determinants of ANC attendance.